Energy Projects, Social Licence, Public Acceptance and Regulatory Systems in Canada: A White Paper - John Colton; Kenneth Corscadden; Stewart Fast; Monica Gattinger; Joel Gehman; Martha Hall Findlay; Dylan Morgan; Judith Sayers; Jennifer Winter; Adonis Yatchew (University of Calgary, 2016)
It has become increasingly difficult in Canada to gain and sustain public acceptance of energy projects. Increased levels of protest, combined with traditional media and social media coverage of opposition, combine to suggest decreased public acceptance of energy projects. Decision-makers have responded accordingly, and a variety of energy projects have either been delayed or put on hold indefinitely. This is true for both conventional and renewable energy projects and in many different regions across the country. A number of proposed energy projects have recently faced opposition from various stakeholder groups. For instance, the decision of the Joint Review Panel for the Northern Gateway Pipeline is being challenged in Canada’s court system. First Nations groups have issued an ultimatum to the Federal Government that it must choose between Site C (a proposed hydro dam) and liquefied natural gas development in B.C. Rapid expansion of wind energy projects in Ontario has engendered lengthy and costly appeals and the rise of an anti-wind social movement. In Nova Scotia, tidal energy development is being positioned as a new renewable energy option; gaining public acceptance is critical in light of recent opposition to wind energy development. As these experiences suggest, not only has the regulatory process become more contentious, but also an apparently new concept — social licence — has had popular appeal. This white paper reports on the results of a year-long interdisciplinary collaboration aimed at identifying and summarizing extant research regarding social licence and related concepts, with a particular emphasis on understanding its implications for public acceptance of energy projects in Canada, and their related regulatory processes. In particular, this research addressed the following questions: 1. What is the history and scope of the term ‘social licence’, both in the context of energy project development and more generally? What are the strengths and limitations of this term? How does it help or hinder ...